Rule Changes and Competitive Balance in Formula One Motor Racing - Camilla Mastromarco; Marco Runkel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
This paper provides an economic explanation of the frequent rule changes in the Formula One (F1) motor racing series. In a two-stage model, the FIA (as the organizer of the F1) first decides whether to change the rules or not, and then the racing teams compete in a contest. It turns out that a rule change reduces the teams' performances, but also improves competitive balance between the teams. The rule change is implemented, if the FIA's revenue gain from the latter effect overcompensates the FIA's revenue loss from the former effect. We provide empirical evidence from F1 seasons in the period 1950-2003 which supports the main implications of the model.
urn:nbn:de:bvb:19-epub-386-4
Keywords: D43; L83; 330; Formula One; Competitive Balance; Contest